Investigation of the THOR Anthropomorphic Test Device for Predicting Occupant Injuries during Spacecraft Launch Aborts and Landing - Somers, Jeffrey T.; Newby, Nathaniel J.; Lawrence, Charles; DeWeese, Richard L.; Moorcroft, David; Phelps, Shean E. (Frontiers in Bioengineering and Biotechnology, 2014)
The objective of this study was to investigate new methods for predicting injury from expected spaceflight dynamic loads by leveraging a broader range of available information in injury biomechanics. Although all spacecraft designs were considered, the primary focus was the NASA Orion capsule, as the authors have the most knowledge and experience related to this design. The team defined a list of critical injuries and selected the Test Device for Human Occupant Restraint (THOR) anthropomorphic test device (ATD) as the basis for new standards and requirements. In addition, the team down selected the list of available injury metrics to the following: head injury criteria (HIC) 15, kinematic rotational brain injury criteria (BRIC), neck axial tension and compression force, maximum chest deflection, lateral shoulder force and displacement, acetabular lateral force, thoracic spine axial compression force, ankle moments, and average distal forearm speed limits. The team felt that these metrics capture all of the injuries that might be expected by a seated crewmember during vehicle aborts and landings. Using previously determined injury risk levels for nominal and off-nominal landings, appropriate injury assessment reference values (IARVs) were defined for each metric. Musculoskeletal deconditioning due to exposure to reduced gravity over time can affect injury risk during landing; therefore a deconditioning factor was applied to all IARVs. Although there are appropriate injury data for each anatomical region of interest, additional research is needed for several metrics to improve the confidence score.